Record of assessment moderation practice (RAMP): survey software as a mechanism of continuous quality improvement - Johnson, Genevieve (Routledge, 2014)
In higher education, assessment integrity is pivotal to student learning and satisfaction, and, therefore, a particularly important target of continuous quality improvement. This paper reports on the preliminary development and application of a process of recording and analysing current assessment moderation practices, with the aim of identifying areas in need of improvement. Specifically, survey software was used to create a record keeping strategy in which unit coordinators documented the assessment moderation and integrity practices in each unit during each study period. Such an online survey approach to record keeping was amenable to data analysis with statistical software, which facilitated identification of trends and anomalies. Instructional staff responded well to the initiative. As is typically the case with monitoring of behaviour, improvements in assessment moderation practices were immediately apparent.